Nanotechnology and society. Current and emerging ethical issues (Berlin, 2008)
"Nanotechnology & Society is a collection of sixteen papers focused on the most urgent issues arising from nanotechnology today and in the near future. Written by leading researchers, policy experts, and nanoethics scholars worldwide, the book is divided into five units: foundational issues; risk and regulation; industry and policy; the human condition; and selected global issues. The essays tackle such contentious issues as environmental impact, health dangers, medical benefits, intellectual property, professional code of ethics, privacy, international governance, and more."